1987
DOI: 10.1099/00221287-133-4-953
|View full text |Cite
|
Sign up to set email alerts
|

Phage tf-1: A Filamentous Bacteriophage Specific for Bacteria Harbouring the IncT Plasmid pIN25

Abstract: Phage tf-1 is a filamentous phage which is about 800 nm in length, 10 nm in width and has slightly tapered ends. The phage was isolated from sewage and formed plaques or propagated only on Escherichia coli, Salmonella typhimurium and Klebsiella oxytoca strains harbouring the IncT plasmid pIN25 at 30 degrees C. It adsorbed in large numbers to pIN25-encoded long thick flexible conjugative pili formed at 30 degrees C and also to the short form of these pili synthesized at 37 degrees C. The reason for the failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Electron microscopy showed that it attached along the pilus shaft ( Fig. 1) and was not specific for the tip or any area close to it, as was the case for tf-1 (Coetzee et al, 1987). This explained why the to@ mutation did not affect it.…”
Section: Adsorption Site Of Filamentous Phage Pfmentioning
confidence: 83%
See 1 more Smart Citation
“…Electron microscopy showed that it attached along the pilus shaft ( Fig. 1) and was not specific for the tip or any area close to it, as was the case for tf-1 (Coetzee et al, 1987). This explained why the to@ mutation did not affect it.…”
Section: Adsorption Site Of Filamentous Phage Pfmentioning
confidence: 83%
“…Phage X has a very wide plasmid specificity range, but it is not known whether this is connected with its insensitivity to the to@ effect. Filamentous phage X-2 (IncX-specific), whose receptor was not identifiable due to poor adsorption (Coetzee et al, 1988), was also inhibited by to@; because of this, it seems very likely that it attaches to the tips of X pili. The inhibition of phage PR64 infection by to@ is noteworthy.…”
Section: Discussionmentioning
confidence: 99%
“…Strain JE2571, carrying the IncFl plasmid R386 (Dennison, 1972) was the indicator for phage fd (see below). Other plasmids belonging to Inc groups C (Sirgel et al, 1981), D (Coetzee et al, 1985a), HI and HI1 (Coetzee et al, 19853), J (Bradley et al, 1982a), S (Coetzee et al, 1986) and T (Bradley et al, 1981 b ;Coetzee et al, 1987) were also used in phage host-range experiments. Constitutive production of conjugative pili by the above plasmids was assessed by the ability of corresponding plasmid-specific phages, described in the same references, to form plaques on lawns of the plasmid-bearing organisms.…”
Section: Methodsmentioning
confidence: 99%
“…Constitutive production of conjugative pili by the above plasmids was assessed by the ability of corresponding plasmid-specific phages, described in the same references, to form plaques on lawns of the plasmid-bearing organisms. Filamentous phage X (Bradley et al, 1981 a) the X-like phages IKe (Khatoon et al, 1972) and 12-2 (Coetzee et al, 1982;, phages PR64FS (Coetzee et al, 1980), fd (Marvin & Hoffmann-Berling, 1963), SF (Coetzee et al, 1986) and tf-1 (Coetzee et al, 1987) were compared serologically with phage X-2 (see Results). The RNA-containing phage C-1 (Sirgel et al, 1981) and filamentous phages X, IKe, PR64FS and fd were used as controls in organic solvent and RNAase susceptibility tests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation